2011
DOI: 10.1002/ps.2313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of camptothecin and hydroxycamptothecin on insect cell lines Sf21 and IOZCAS‐Spex‐II

Abstract: The results confirm the existence of the mitochondrial-dependent pathway of apoptosis induced by CPT and HCPT in Sf21 and IOZCAS-Spex-II cell lines. Further investigations are required to reveal the mitochondrial mechanisms and regulation of caspase activation during apoptosis. These studies will provide basic knowledge needed to understand the mechanisms of action of CPT and to develop CPT and its derivatives as insecticides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…In all experiments, IOZCAS-Spex-II cells were pretreated with CPT and HCPT according to the procedure described in our previous studies [16]. The Topo1 was extracted from IOZCAS-Spex-II cells, and the specific activity of the nuclear extract in each sample was determined using the method described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all experiments, IOZCAS-Spex-II cells were pretreated with CPT and HCPT according to the procedure described in our previous studies [16]. The Topo1 was extracted from IOZCAS-Spex-II cells, and the specific activity of the nuclear extract in each sample was determined using the method described above.…”
Section: Methodsmentioning
confidence: 99%
“…To find new CPT-derived insecticides with improved efficacy and to determine the potential structural factors required for the biological activity of CPT analogues, a series of novel CPT derivatives have been semi-synthesized, and some of them were found toxic to armyworms ( Mythimna separate Walker) and coconut palm beetles ( Brontispa longissima Gestro) [14], [15]. In our previous studies, we found that 0.1–30 µM CPT treatment to IOZCAS -Spex-II cells (established from beet armyworms, Spodoptera exigua Hübner) induce cell apoptosis [16]. Thus, these previous findings intrigue us to explore CPT as a lead compound of an insect control agent, and to investigate the possibility of exploring a new Topo1-targeted botanical insecticide.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these results, Zhang et al recently revealed that CPT caused Sf21 and IOZCAS‐Spex‐II cell apoptosis via a mitochondrial‐dependent apoptosis signal transduction pathway, suggesting that its mode of action may be related to apoptosis. Moreover, pretreatment with CPT led to reduction in both the enzymatic activity and the steady accumulation of the topo I protein in IOZCAS‐Spex‐II cells despite upregulation of its mRNA expression in response to the treatment . In connection with these efforts, in order to find new CPT‐derived insecticides with improved profiles and to clarify the SARs of campothecin analogs, a number of CPT derivatives modified in the different positions have been synthesized and evaluated for their insecticidal activity against some important insect pests by our group; among which, some compounds exhibited insecticidal activity equal to or higher than that of CPT.…”
Section: Biological Activity Of Cpt and Related Derivativesmentioning
confidence: 99%
“…Consistent with these data, Zhang et al . have reported that CPT caused Sf21 and IOZCAS‐Spex‐II cell apoptosis via a mitochondrial‐dependent apoptosis signal transduction pathway …”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of action of CPT as a botanical pesticide is still unknown. Recent observations showed that CPT could induce apoptosis in different insect cell lines, suggesting that its mode of action may be related to apoptosis …”
Section: Introductionmentioning
confidence: 99%